311 FROM ONE FRONT DOOR TO ANOTHER: OUTCOMES OF PATIENTS DIRECTLY DISCHARGED FROM THE FRAILTY AT THE FRONT DOOR SERVICE. (25th October 2022) - Griffith, V; Murphy, R; Sheil, O; Roche, E; Devaney, T; Geoghegan, J; Robinson, S; Waters, R; O'Donnell, M; Canavan, M
Abstract: Background: The Frailty at the Front Door service is a novel service that provides comprehensive geriatric assessment in the emergency department for older adults who have an unplanned emergency presentation to hospital. It is important to monitor outcomes of patients discharged by the service to ensure appropriate patient selection. Methods: Patients over the age of 75 with a Manchester Triage Score of between three and five and a possible frailty syndrome are eligible for review by the service. After initial review patients are either discharged directly or recommended for admission. We reviewed the outcomes of patients who were discharged directly after Emergency Department (ED) assessment by the service. Results: Discharge disposition was available for review in 413 (95%) of patients since initiation of the service in October 2021. 30% (n= 122) of patients were discharged directly after initial ED review. Elevated 4AT score (p = 0.002) but not frailty (p = 0.80) was associated with decreased chances of direct discharge. Of patients discharged directly from ED 13% were reviewed post discharge by the community integrated care team (GICOP), with 43% of these reviews taking place within 30 days. Overall, 16% of patients discharged directly represented to ED within 30 days. There was a trend towards lower rates of representation to ED among patients who were seen by GICOP after discharge from ED (p = 0.12). Conclusion: There was a high rate of direct discharge after review by the service, with low rates of representation to hospital. While limited by low numbers there was a trend towards lower representation rates in patients reviewed post-discharge by the integrated care team. Future quality improvement initiatives will aim to improve the integration between the services and highlighting patients who would benefit from more timely reviews.